Collective agency in the implementation of computerized clinical decision support: an interpretive description study. - Fernando, Manasha; Naicker, Sundresan; Abell, Bridget; McPhail, Steven M.; Tyack, Zephanie (JBI Evidence Implementation, 2026)
Introduction: Digital health interventions, such as computerized clinical decision support systems (CDSSs), often falter due to resource constraints, misaligned workflows, and limited engagement from key users and stakeholders. Little is known about how research-to-practice professionals navigate these challenges. Aim: This study sought to understand how CDSSs can be integrated into routine clinical practice and the contextual factors that influence translation. Methods: Using interpretive description methodology, we conducted semi-structured interviews with 32 participants and three focus groups involving 11 participants to explore perspectives and experiences of translating implementation knowledge into practice. Participants included experts in health services research, implementation science, and health informatics. Convenience, purposive, and snowball sampling were used to recruit participants. Results: The findings describe how CDSS implementation is a socially driven process. Success was framed in terms of harnessing collective agency—building trust, fostering collaboration, and empowering people to work toward shared understanding. This process involved (1) laying the groundwork by engaging those affected; (2) making implementation accessible by adapting theories into usable tools; and (3) breaking slow progress by learning from past efforts and strengthening clinical–academic partnerships. Conclusions: The findings highlight opportunities for developing accessible tools and partnerships and embedding experiential knowledge. Practice recommendations are offered to support CDSS implementation teams, including setting up regular feedback channels, using memoranda of understanding, and checklists for implementation. http://links.lww.com/IJEBH/A501